THE IMPORTANCE OF INTERDISCIPLINARY HARMONIZATION (INTEGRATION) IN MATHEMATICS LESSONS - Gafforova Sarvinoz (Bright Mind Publishing, 2025)
This article covers the theoretical and practical foundations of interdisciplinary integration in mathematics lessons. The importance of an integrated approach in developing students' knowledge, thinking, and skills in solving life problems is analyzed. In particular, the inextricable link between mathematics and physics, computer science, geography, biology, and technology is revealed through examples. Also, effective methods for organizing interdisciplinary lessons are considered - a project-based approach, integrated lessons, and cross-curricular connections. The article proves the positive impact of integration on the quality of education through practical examples taken from real lessons. The results of the study serve as an important scientific and practical basis for the effective organization of mathematics lessons and improving the methodological approach based on modern educational requirements.
Keywords: Integration, interdisciplinary connection, mathematics, harmonization, didactics, modern education.